2010
DOI: 10.1103/physrevb.81.075105
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure structural study of fluoro-perovskiteCsCdF3up to 60 GPa: A combined experimental and theoretical study

Abstract: The structural behaviour of CsCdF 3 under pressure is investigated by means of theory and experiment. High-pressure powder x-ray diffraction experiments were performed up to a maximum pressure of 60 GPa using synchrotron radiation. The cubic P m3m crystal symmetry persists throughout this pressure range. Theoretical calculations were carried out using the full-potential linear muffin-tin orbital method within the local density approximation and the generalized gradient approximation for exchange and correlatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 45 publications
(48 reference statements)
3
14
0
Order By: Relevance
“…Assuming that the optical transitions across the band gap were direct, the high-energy linear absorption component was extrapolated to the energy axis to yield a band gap energy of ε g = 5.8 eV (214 nm), in close agreement with the previously determined value[86]. Band structure calculations for pure CsCdF 3 produce band gap energies ranging from ~4.2 eV to ~7 eV[89,135], also in agreement. The calculations also predicted the existence of indirect band gaps at lower energies -however, the probabilities of indirect optical transitions are significantly lower than…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Assuming that the optical transitions across the band gap were direct, the high-energy linear absorption component was extrapolated to the energy axis to yield a band gap energy of ε g = 5.8 eV (214 nm), in close agreement with the previously determined value[86]. Band structure calculations for pure CsCdF 3 produce band gap energies ranging from ~4.2 eV to ~7 eV[89,135], also in agreement. The calculations also predicted the existence of indirect band gaps at lower energies -however, the probabilities of indirect optical transitions are significantly lower than…”
supporting
confidence: 71%
“…RbMgF 3 has approximate lattice parameters a = 5.83 Å, b = 5.83 Å, c = 14.20 Å and space group P6 3 /mmc [88]. CsCdF 3 has approximate lattice parameter a = 4.47 Å and space group Pm 3m [89].…”
Section: Fluoroperovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…For additional literature relating to the supporting information, see Aguado et al (2008), Vaitheeswaran et al (2010), Martin et al (2006), Jones (1979), Zhou et al (2011), Yakovlev et al (2009Yakovlev et al ( ), Å sbrink et al (1993 and Rousseau et al (1974).…”
Section: Related Literaturementioning
confidence: 99%
“…Particularly RbHgF3 is a superior choice for the high-class lens materials because it does not suffer with birefringence, which can make design of lenses problematic [2][3][4][5][6][7][8][9][10]. Comprehensive experimental studies are available on their interesting structural properties which is being confirmed that under consideration compound crystallizes in cubic structure and it do not unveil any phase transition under varies pressure and temperature [11][12].…”
Section: Introductionmentioning
confidence: 99%